PHYSICAL EXERCISE IN THE PERSON WITH DEPRESSIVE DISORDER: A SYSTEMATIC REVIEW OF THE LITERATURE - Inês de Jesus Rocha; Carla Alexandra Fundevila Barros; Ana Maria Pinto Mateus; Rosa Cristina Rodrigues Correia; Helena Castelão Figueira Carlos Pestana; Luís Sousa (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Background: Depressive disorder is one of the most common forms of mental disorder and one of the greatest causes of health problems nowadays. There has been a need to combine the pharmacological approach with adjuvant treatment such as psychoterapy and physical exercise in the treatment of this disorder. Objective: To identify the benefits of physical exercise in the person with depressive disorder. Method: Systematic Review of Literature that was based on the recommendations of the Joanna Briggs Institute on PICO strategy and based on PRISMA, the research question raised was "What are the benefits of physical exercise in people with Depressive Disorder?". The research was carried out using the electronic database platforms: EBSCOHost and B-on. Results: A sample of nine studies were included that fulfilled the eligibility and methodological quality criteria, where the type, volume, frequency and duration of the physical exercise practiced in each of the studies were described and analyzed. Conclusions: The results obtained allow us to conclude that regardless of the frequency, duration and intensity of physical exercise in depressive disorder, this decreases the depressive symptoms, improving also the physical fitness, the cognitive function and the well-being of the person with this disorder.